Argon plasma reduced Pt nanocatalysts supported on carbon nanotube for aqueous phase benzyl alcohol oxidation - Zhou, Chunmei (2013)
Carbon nanotube supported Pt nano-catalyst was prepared by facile glow discharge plasma reduction operated at room temperature. The low-temperature plasma reduced Pt nanoparticles exhibited uniform size distribution and an average particle size of around 2.3 nm. Electrochemical measurements also proved that the plasma reduced Pt catalyst has remarkably higher active surface area comparing to the conventional hydrogen thermally reduced sample (3.6 nm in diameter). The plasma reduced Pt/CNT catalysts exhibited significantly higher conversion in benzyl alcohol aerobic oxidation compared to the hydrogen reduced Pt catalyst. Nonetheless, no obvious difference was found on the catalytic activity in terms of turn over frequency (TOF) between the plasma and hydrogen reduced Pt/CNT catalysts. Therefore, low temperature plasma reduction can effectively enhance Pt dispersion without changing its intrinsic catalytic property.